2019
DOI: 10.32604/jrm.2019.04276
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of Thermoplastic Starch Induced by UV Radiation

Abstract: Among biopolymers, thermoplastic starch (TPS) is a good candidate to obtain biomaterials because of its natural origin, biodegradable character, and processability. Exposure to ultraviolet (UV) radiation causes significant degradation of starch-based materials, inducing photooxidative reactions which result in breaking of polymer chains, production of free radical, and reduction of molar mass. These changes produce a deterioration of TPS mechanical properties, leading to useless materials after an unpredictabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…They tentatively justified this trend with the crosslinking caused by the pulsed light UV radiation. A similar result was also obtained by Quispe et al, 63 who attributed the mass loss in the starch films during UV storage to the loss of plasticizer by evaporation, noticing the weight loss seemed correlated with the lowmicrobial load present during the degradation process. Shujun et al 64 investigated the degradation of starch/ polyethylene film and observed that film exposed to the air had a reduction in weight (5.69% for 30 days), which attributed to due to the strong light-oxidation degradation.…”
Section: Mass Losssupporting
confidence: 85%
“…They tentatively justified this trend with the crosslinking caused by the pulsed light UV radiation. A similar result was also obtained by Quispe et al, 63 who attributed the mass loss in the starch films during UV storage to the loss of plasticizer by evaporation, noticing the weight loss seemed correlated with the lowmicrobial load present during the degradation process. Shujun et al 64 investigated the degradation of starch/ polyethylene film and observed that film exposed to the air had a reduction in weight (5.69% for 30 days), which attributed to due to the strong light-oxidation degradation.…”
Section: Mass Losssupporting
confidence: 85%
“…Moreover, the photocatalytic degradation of PZQ was documented [ 48 , 49 ]. The photons of sunlight wavelengths are absorbed by starch polymer material [ 50 , 51 ]. Therefore, the degree of starch opacity may be suitable for applications in which there is light protection.…”
Section: Discussionmentioning
confidence: 99%
“…Essa evaporação foi causada pela secagem natural dos biofilmes durante o armazenamento dos mesmos na câmara de fotodegradação, o que permitiu o início da biodegradação (Oliveira et al, 2019). Quispe et al (2019) produziram filmes de amido e ao realizarem o ensaio de fotodegradação, observaram que houve perda de massa dos biopolímeros, e atribuíram isso à baixa carga microbiana presente durante o processo de degradação.…”
Section: F) Fotodegradaçãounclassified